2005
DOI: 10.1016/j.cub.2005.03.049
|View full text |Cite
|
Sign up to set email alerts
|

RIN1 Is an ABL Tyrosine Kinase Activator and a Regulator of Epithelial-Cell Adhesion and Migration

Abstract: RIN1 is a directly binding ABL tyrosine kinase activator in cells as well as in a defined-component assay. In response to environmental changes, this novel signal pathway mediates actin remodeling associated with adhesion and migration of epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
148
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 49 publications
5
148
0
Order By: Relevance
“…They showed that Rin1 interacts with GTP-Ras and thereby competes with Raf1 (28). More recent work from the same group indicates that Rin1 interacts with the tyrosine kinase Abl and that via phosphorylation of CRK and CRKL, Rin1 plays a role in actin remodeling and cell migration in epithelial cells and neurons (30). Abl binds Rin1 through the PRD and SH2 domains of Rin1, the same domains that we have shown to interact with STAM2 and EGFR, respectively.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…They showed that Rin1 interacts with GTP-Ras and thereby competes with Raf1 (28). More recent work from the same group indicates that Rin1 interacts with the tyrosine kinase Abl and that via phosphorylation of CRK and CRKL, Rin1 plays a role in actin remodeling and cell migration in epithelial cells and neurons (30). Abl binds Rin1 through the PRD and SH2 domains of Rin1, the same domains that we have shown to interact with STAM2 and EGFR, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…It is composed of several functional domains: SH2 and proline-rich (29) domains in the N-terminal region and Vps9 and Ras association domains in the C-terminal region. Recent studies have shown that through its interaction with Abl tyrosine kinase, Rin1 mediates actin cytoskeleton remodeling associated with migration and adhesion of epithelial cells (30). Our previous work suggested that Rin1 is an exchange factor for small GTPase Rab5, whose overexpression stimulates EGF-mediated endocytosis (31).…”
mentioning
confidence: 99%
“…Cellular tyrosine phosphatases may be responsible for restricting c-Abl activity, as vanadate exposure resulted in activation of c-Abl in all expressing cells. Reciprocal regulation, whereby a substrate interacts with and activates C3G is a target and effector of c-Abl function A Mitra and V Radha c-Abl to phosphorylate itself is known in the case of Abl targets (Shishido et al, 2001;Hu et al, 2005), but C3G co-expression did not alter c-Abl activity. Phosphorylation of another c-Abl substrate, CrkII, also occurred only in cells showing detachment and condensed chromatin.…”
Section: C3g Is a Target And Effector Of C-abl Functionmentioning
confidence: 99%
“…RIN1 expression was attenuated using short interfering RNA (siRNA) as previously described (28) or short hairpin RNA (shRNA)-mediated RNA interference. The shRNA primers were designed using the BLOCK-iT RNAi Designer algorithm (Invitrogen).…”
mentioning
confidence: 99%
“…The shRNA primers were designed using the BLOCK-iT RNAi Designer algorithm (Invitrogen). Primers were attached to a U6 promoter via PCR and subsequently cloned into the M4 lentiviral vector (28) modified to include a blasticidin resistance marker. Virus stocks were generated by standard techniques (28).…”
mentioning
confidence: 99%